Impacts of an Early Stage Education Intervention on Students' Learning Achievement : Evidence from the Philippines - Yamauchi, Futoshi; Liu, Yanyan (World Bank, Washington, DC, 2013)
This paper examines the impact of a large supply-side education intervention in the Philippines, the Third Elementary Education Project, on students' national achievement test scores. It finds that the program significantly increased student test scores at grades 4 to 6. The estimation indicates that two-year exposure to the program increases test scores by about 4.5 to 5 score points. Interestingly, the mathematics score is more responsive to the education reform than are other subjects. The analysis also finds that textbooks, instructional training of teachers, and new classroom construction particularly contributed to these outcomes. The empirical results imply that early-stage investment improves student performance at later stages in the elementary school cycle, which suggests that social returns to such an investment are greater than what the current study demonstrates.